2007
DOI: 10.1167/iovs.06-1184
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antigen-Presenting Cells in Fresh and Cultured Human Corneas Using Novel Dendritic Cell Markers

Abstract: This is the first demonstration that human corneas harbor populations of Langerin(+)/CD1a(+)/HLA-DR(+) LCs and DC-SIGN(+) DCs in a distribution pattern similar to that in the skin. Few APCs are in a mature state (DC-LAMP(+)). Given the reduced but not complete depletion of APCs during organ culture, these grafts still bear a potential risk for rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 37 publications
8
75
0
9
Order By: Relevance
“…The presumption that the dendritic cells observed with CCM are Langerhans cells and not another subset of dendritic cells is supported by previous findings that Langerhans cell‐specific surface markers are expressed by dendritic cells in the corneal and limbal epithelium 53, 54. Due to the fact that there are no animal studies for inflammatory neuropathies and that cell differentiation in the current study was based on morphological aspects, it is speculative to specify which immunological subtype was counted.…”
Section: Discussionsupporting
confidence: 64%
“…The presumption that the dendritic cells observed with CCM are Langerhans cells and not another subset of dendritic cells is supported by previous findings that Langerhans cell‐specific surface markers are expressed by dendritic cells in the corneal and limbal epithelium 53, 54. Due to the fact that there are no animal studies for inflammatory neuropathies and that cell differentiation in the current study was based on morphological aspects, it is speculative to specify which immunological subtype was counted.…”
Section: Discussionsupporting
confidence: 64%
“…However, studies have also demonstrated that there are resident CD11b-positive cells present in the unwounded corneal stroma (Mayer et al, 2007). Therefore, although the authors believe it is likely most of the infiltrating cells detected in these experiments are bone marrow-derived cells, we cannot exclude the possibility that some cells are locally recruited CD11b-positive cells.…”
Section: Discussionmentioning
confidence: 69%
“…14 In our retrospective analysis, we found that even longer storage times of 421 days of organ culture led to a statistically significant decreased risk of immune reactions. From the in vitro results of the kinetics regarding the stromal APC decrease with the fastest depletion of stromal APCs during the first 7 days of organ culture 13 and our observation that the highest rate of rejections was in the group of grafts with storage times below 14 days compared with longer storage periods (see Figure 3) it might be concluded that stromal and not only epithelial DCs have an important role in corneal allograft rejection.…”
Section: Discussionmentioning
confidence: 73%
“…8 It has been shown that the number of LCs and DCs slowly decreases during organ culture, [9][10][11][12][13] although it seems that they do not vanish completely. Mayer et al 13 found that human corneas harbour different populations of LCs and DCs in a distribution pattern similar to that in the skin. In their kinetic study of DCs in organ culture, they found a significant decrease of APCs within the first 3 weeks of organ culture.…”
Section: Introductionmentioning
confidence: 99%